The effect of corporate social responsibility, capital structure, and current ratio on profitability with firm size as moderating variables on companies in the Jakarta Islamic Index (JII) 2016-2020 - Arum Teguh Fitriyani; Arna Asna Annisa (Journal of Islamic Economics, Management, and Business (JIEMB), 2021)
The establishment of a business is certainly based on several things, one of which is to get profit or integrity. A company's profits will certainly increase and decrease, things that can affect the rise and fall of a company's profits include the disclosure of corporate social responsibility, capital structure, and current ratio. The purpose of this research is to find out the influence of corporate social responsibility, capital structure, and current ratio on profitability moderated by the firm size . This research is quantitative research, with the research population in companies listed on the Jakarta Islamic Index amounting to 30 companies. The sampling technique uses purposing sampling techniques, so that for sample withdrawal in this research, 12 companies registered with JII for the period 2016-2020. The analytical techniques in this research use descriptive statistical data analysis. The results of this research show that corporate social responsibility variables, capital structure, and current ratio together have a significant influence on profitability variables. Corporate social responsibility has a significant positive influence on profitability, capital structure has a significant negative influence on profitability, current ratio does not have a significant influence on profitability, Firm Size does not have a significant influence on profitability, the firm size is able to moderate corporate social responsibility, capital structure, and current ratio on profitability.